(untitled) (Journal of Information Technology and Digital World, 2023)
Healthcare management using blockchain technology refers to the use of blockchain to improve the efficiency, security and privacy of healthcare data management. Blockchain enables the creation of a decentralized, tamper-proof database that can be shared among healthcare providers, patients, and other stakeholders. This can enhance the coordination and sharing of healthcare data, streamline the administrative processes, reduce costs, and improve patient outcomes. This abstract provides an overview of healthcare management using blockchain, highlighting its benefits and challenges, as well as its potential applications in healthcare. The major reason that paves way for the exploration of blockchain in health care management is its capabilities to secure the information’s from cyber-attacks, fraud, and unauthorized access and allow an equitable and transparent data management without the need for a central authority or intermediary, making sure that patients have greater control over their own data. This method can also enable the secure exchange of health data between different healthcare systems and providers, promoting interoperability and improving patient care, by removing the need for intermediaries, blockchain can help streamline the administrative processes, reducing costs and improving the efficiency of healthcare delivery and tracking of medical products and devices throughout the supply chain, helping to prevent counterfeiting and ensuring patient safety. Overall, the use of blockchain in healthcare management has the potential to improve the quality of care, reduce costs, and increase patient satisfaction. However, there are also challenges to be addressed, such as regulatory compliance, interoperability, and scalability.